Morphometrics of macrotermes bellicosus (African mound termite) (blattodea: termitidae) and the impact of its saliva amylase on the strength of termitarium soil (2012)
The aim of this study was to investigate the morphology of Macrotermes bellicosus present on some parts of the University of Ibadan and to determine the effect of the saliva of termites on the strength of termitarium. Termites were collected from 8 termitaria on Parry Road, University of Ibadan and characteristics morphometrics were measured using stage graticules (10mm) on Microscope. Amylase analysis was conducted to determine the activity of the saliva content in the termitarium soil using Phadebas® α-amylase test method. Bricks were molded from the termitarium soil while pressure gauge was used to measure the strength via cracking of molded brick from the soil. The studies revealed that the length of head capsule for workers ranged from 0.16mm to 0.24mm, while those of soldiers ranged from 0.42mm to 0.68mm. The body length of workers ranges from 0.5mm to 0.7mm and that of soldiers ranged from 1.1mm to 1.4mm this confirmed that the soldiers were bigger. The amylase analysis showed that termitarium soil contained α-amylase while it was undetected in the control soil. The α-amylase activities for the termitarium soil was 41 unit per liter, 47 unit per liter and 56 unit per liter at dilutions 10-1M, 10-2M and 10-3M respectively. The bricks molded from the termitarium soil and the control soil all cracked at a pressure less than 1MPa; however bricks molded from clayey and mature termitarium showed higher strength of materials. It may be concluded that the modification of the termitarium soil’s physical properties and the selection of clay particles during construction activities by termites had more contribution to strength than the presence of α-amylase in the termitarium soil.